Improved Clinical Workflow for Whole-Body Patlak Parametric Imaging Using Two Short Dynamic Acquisitions - Wang, Hui; Miao, Ying; Yu, Wenjing; Zhu, Gan; Wu, Tao; Zhao, Xuefeng; Yuan, Guangjie; Li, Biao; Xu, Huiqin (Frontiers in Oncology, 2022)
Objective: We sought to explore the feasibility of shorter acquisition times using two short dynamic scans for a multiparametric PET study and the influence of quantitative performance in shortened dynamic PET. Methods: Twenty-one patients underwent whole-body dynamic 18F-FDG PET/CT examinations on a PET/CT (Siemens Biograph Vision) with a total scan time of 75 min using continuous-bed-motion for Patlak multiparametric imaging. Two sets of Patlak multiparametric images were produced: the standard MRFDG and DVFDG images (MRFDG-std and DVFDG-std) and two short dynamic MRFDG and DVFDG images (MRFDG-tsd and DVFDG-tsd), which were generated by a 0-75 min post injection (p.i.) dynamic PET series and a 0-6 min + 60-75 min p.i. dynamic PET series, respectively. The max, mean and peak values of the standard and two short dynamic multiparametric acquisitions were obtained and compared using Passing & Bablok regression and Bland & Altman analysis. Results: High correlations were obtained between MRFDG-tsd and MRFDG-std, DVFDG-tsd and DVFDG-std for both normal organs and all lesions (0.962 ≦ Spearman’s rho ≦ 0.982, P < 0.0001). The max, mean and peak values of the standard and two short dynamic multiparametric acquisitions also agreed. For normal organs, the Bland-Altman plot showed the mean bias of MRFDG-max, MRFDG-mean and MRFDG-peak were -0.002 (95%CI: -0.032 0.027), -0.002 (95%CI: -0.026 0.023), -0.002 (95%CI: -0.026 0.022), respectively. And the mean bias of DVFDG-max, DVFDG-mean and DVFDG-peak were -3.3 (95%CI: -24.8 18.2), -1.4 (95%CI: -12.1 9.2), -2.3 (95%CI: -15 10.4), respectively. For lesions, The Bland-Altman plot showed a mean bias of MRFDG-max, MRFDG-mean and MRFDG-peak were -0.009 (95%CI: -0.056 0.038), -0.004 (95%CI: -0.039 0.031), -0.004 (95%CI: -0.036 0.028), respectively. And the mean bias of DVFDG-max, DVFDG-mean and DVFDG-peak were -8.4 (95%CI: -42.6 25.9), -4.8 (95%CI: -20.2 10.6), -4.0 (95%CI: -23.7 15.6), respectively. Conclusions:This study demonstrates the feasibility of using two short dynamic scans which include the first 0-6 min and 60-75 min scans p.i. for Patlak multiparametric images, which can increase patient throughout for parametric analysis.